The Happy Ever After Playlist - Jimenez, Abby (New York : Forever, 2020)
"Sloan Monroe can't catch a break. Two years after losing her fiancé, her life consists of cemetery visits, unorthodox art projects, and drinking sessions with her best friend Kristen. So when a dog dashes in front of her car and gets her a ticket for obstructing traffic, [she's] at her wits' end. But after meeting the ridiculously attractive and charming owner of the trouble-making retriever, she begins to think that maybe her luck has finally started to turn around"--
Keywords: Man-woman relationships -- Fiction; Rock musicians -- Fiction; Dogs -- Fiction; Romance fiction